PERBANDINGAN PEMERTAHANAN KEARIFAN LOKAL DALAM UPAYA PELESTARIAN LINGKUNGAN DALAM NOVEL BERTEMA LINGKUNGAN - Purwati Anggraini (Universitas Muhammadiyah Surakarta, 2019)
Local wisdom teaches people to live wiser and wiser lives, one of which is manifest in protecting their environment. However, local wisdom that could have been inherited from generation to generation began to be eroded by the flow of modernization and globalization. For this reason, it is very rare to find people who still apply local wisdom as a way of life, including in their efforts to respond to their environment. This has an impact on the increasingly damaged natural environment. For this reason, efforts need to be made to reduce events like this, one of which is by reminding others through novel studies. Thus the need for research with the object of environmental-themed novel studies. This study uses a descriptive comparative method with an ecological approach. The object of the study is a novel entitled Sokola Rimba by Butet Manurung and Sebuah Wilayah yang Tidak Ada di Google Earth by Pandu Hamzah. The purpose of the study is to produce a description of the retention of local wisdom that can anticipate or at least inhibit environmental damage. The results of this study indicate that the community in the novel setting seeks to preserve nature, maintain the harmonization of life with nature through local wisdom that is held firmly. Communities believe in the detrimental effects of natural damage when they forget local wisdom. The local wisdom they hold firm includes knowledge, values, skills, natural resources, decision-making mechanisms, rituals, and local beliefs.